Robust and adaptive terrain classification and gait event detection system - Shaikh, Usman Qamar; Shahzaib, Muhammad; Shakil, Sadia; Bhatti, Farrukh A; Aamir Saeed, Malik (Heliyon, 2023)
Real-time gait event detection (GED) system can be utilized for gait analysis and tracking fitness activities. GED for various types of terrains (e.g., stair-walk, uneven surfaces, etc.) is still an open research problem. This study presents an inertial sensor-based approach for real-time GED system that works for diverse terrains in an uncontrolled environment. The GED system classifies three types of terrains, i.e., flat-walk, stair-ascend and stair-descend, with an average classification accuracy of 99%. It also accurately detects various gait events, including, toe-strike, heel-rise, toe-off, and heel-strike. It is computationally efficient, implemented on a low-cost microcontroller, works in real-time and can be used in portable rehabilitation devices for use in dynamic environments.
Keywords: Gait event detection (GED); Terrain classification; Adaptive